Sarining Pamutus: Mantra Ruwat Jawa Kuno dalam Catatan Lontar Bali - Pande Putu Abdi Jaya Prawira (Manuskripta, 2026)
The Sarining Pamutus (SP) text is a Balinese palm-leaf manuscript containing Old Javanese prose mantras used for ruwat (purification). This philological study aims to describe the structure and content of the SP text and trace Old Javanese cultural elements in Balinese manuscripts. Three SP manuscripts were identified at Udayana University and the Bali Cultural Documentation Center. Overall, the 23 mantra subtexts feature key characteristics: affirming the chanter's spiritual authority, anthropogony linked to divine mythology (Kāma and Rati), microcosmic cosmology viewing the body as a universe, purification through rituals (panglukatan, pangentas, and palepasan), and symbols of ultimate stillness. These mantras emphasize uniting the spirit with supernatural power to transform evil into good. Further research is required to explore the practical use of these mantras in rituals and reconstruct the transmission of Old Javanese intellectual traditions in Bali. === Teks Sarining Pamutus (SP) merupakan naskah lontar Bali berisi kumpulan mantra Jawa Kuno berbentuk prosa panjang untuk tradisi ruwat (penyucian). Penelitian filologi ini bertujuan mendeskripsikan struktur dan isi teks SP serta melacak jejak budaya Jawa Kuno dalam naskah Bali. Tiga naskah SP diidentifikasi di Perpustakaan Lontar Universitas Udayana dan Pusat Dokumentasi Kebudayaan Bali. Secara umum, 23 subteks mantra di dalamnya memiliki karakteristik utama: penegasan otoritas spiritual penutur, antropogoni yang terhubung dengan mitologi dewa (Kāma dan Rati), kosmologi mikrokosmos yang memandang tubuh sebagai alam semesta, penyucian melalui ritual (panglukatan, pangentas, dan palepasan), serta simbol pencapaian keheningan tertinggi. Mantra-mantra ini menekankan penyatuan roh dengan kekuatan gaib untuk mengubah kejahatan menjadi kebaikan. Penelitian lebih lanjut diperlukan untuk mengeksplorasi aspek praktis mantra dalam ritual serta merekonstruksi tradisi intelektual Jawa Kuno di Bali.